Fabrication and characterization of nickel-coated polyethylene terephthalate supported mangabese dioxide thin-film electrochimical capacitor prototypes - Wee, Boon Hong (Universiti Malaysia Sarawak (UNIMAS), 2011)
Energy deficiency has always been a pressing global concern especially during the midst of the ditch of the world's oil reserve meagrely supplying 80% to 90% of the current worldwide energy consumption. The increasing demand of fossil fuels at the turn of the millennium can be incontrovertibly associated with the exponential growth of human population resulted in the worrying surge of oil's price where in search of replacement for this finite resources is direly needed. In today's society, dramatic advancement in modern electrical technologies which we are heavily dependent on has altered the globe's energy requirement to cheaper, cleaner, durable, efficient and sustainable energy resources. In respond to the paradigm-shift, concerted efforts are being focused on the development of high performance energy-storage systems that are capable of meeting the ever increasing energy demand of various device applications., As such, our present study entails the fabrication of manganese dioxide (Mn02) thin film electrochemical capacitor prototypes via novel prototyping process (Patent Pending PI 20094040) of core interest focused predominantly on utilizing ubiquitous and environmentally benign materials, optimizing electrode configuration and nanostructuring of electroactive material (Mn02). Of all electroactive materials, manganese dioxide is specially selected as it not only fulfills the basic criteria for electrode materials as being cheap and toxicologically harmless, but also exhibits superior capacitive behaviour comparable to that of ruthenium dioxide. Ruthenium dioxide despite being regarded as the quintessential electrode material to date, its potential applications are commercially unviable where the limiting factor mainly lies in the expensive cost of production. The rapid prototyping process which we have developed entails the deposition of manganese dioxide thin films on metallized poly(ethylene terephthalate) substrate using the novel horizontal submersion approach. Interdigitated array (IDA) electrodes of different configurations were generated using a computer interfaced cutting plotter. Subsequently a conformal agar-based gel electrolyte layer containing dissolved Na2SO4 salt was deposited by solution casting directly onto the IDA electrodes. These prototypes of different IDA electrode configurations were studied using various established characterization techniques. Both electrochemical and material characterizations of the thin-film Mn02 electrochemical capacitor prototypes showed promising electrochemical properties with excellent capacitive performance and cycling reversibility. Morphological characterizations showed that the deposited manganese dioxide thin films were largely nanoparticulate in nature and possess high electrochemically active surface area. Noticeable morphological changes of Mn02 film were observed during voltammetric cycling in which the film was slowly transformed into a well-organized and interconnected petal-like microstructure. As a result, Mn02 electrodes of enhanced cycling stability and capacitive behaviour were obtained. However, the physicochemical mechanisms that governed the observed morphological changes which led to the formation of foregoing microstructure remained unclear. Much research on the synthesis of nanomaterials is imperatively necessary to better understand the myriad of fundamental interactions at nanoscale level. Electrodes of desired microstructures can therefore be finely architectured to obtain enhanced capacitive performance. Cyclic voltammetry studies on Mn02-based electrochemical capacitors with dual planar IDA electrode configurations showed that the capacitive performance is more superior compared with ECs of conventional parallel electrode configuration in terms of the specific capacitance, cycling stability and coulombic efficiency. Electrochemical impedance spectroscopy provides complimentary data to that obtained by cyclic voltammetry. The impedance characteristics of Mn02-based electrode were measured at predetermined frequency range and amplitude of alternating/direct current potential. A Nyquist plot of Mn02-based electrochemical capacitors with IDA electrode configurations indicated distinctive impedance responses which include: 1) a nearly pure capacitive behaviour represented by vertical plot of phase angle approximate to at low frequencies, 2) a diffusion controlled behaviour represented by inclined plot of phase angle approximate to it/4 at intermediate frequencies, and 3) a purely resistive behaviour represented by depressed semicircular arc at high frequencies. The exceptional capacitive performance of EC prototypes of IDA electrode configuration could be attributed to the enhanced ionic conductivity associated with the shorter ionic diffusion path length and utilization of electroactive materials. The major advantage of IDA electrode configuration is that each pair of electrode array can be potentiostated individually and hence resulted in a higher reaction kinetic by providing a shorter diffusion path length between adjacent electrodes for redox electroactive species. Despite its long-standing merits as the cathode electrode of commercial batteries, the Mn02-based electrode is currently being extensively studied for electrochemical capacitor applications. The functionalities of Mn02-based electrodes have inspired an attempt to fabricate novel hybrid energy storage prototype which comprises a battery and an electrochemical capacitor being integrated as a single embodiment. It is denoted as the Hybrid Batt-EC prototype which consists of two Mn02-based EC prototypes with IDA electrode configuration 2, and a piece of galvanized zinc inserted between these IDA EC prototypes. Chronopotentiometry evaluation of this hybrid device showed encouraging results with energy density of 1.17 x 10-3 Ah or 1.17 mAh could be obtained at a discharge current of 0.01 mA. It is envisaged that nanostructuring of electroactive materials offers a more accurate and precise control on the microstructures and porosity (uniform distribution of pores) of desirable electrochemical characteristic. It is recommended that future works should address the effect of microstructural parameters, namely film thickness and homogeneity, grain size, porosity and electrochemically active surface area, and optimized interdigitated array (IDA) electrode configurations.